Pagamento por serviços ambientais: perspectivas para a proteção e uso dos recursos naturais - SÁ, João Daniel Macedo (Universidade Federal do Pará, 2017)
Payment for environmental services (PES) is a collective strategy which incorporates a new model of management for public policies and private instruments for environmental conservation. This work analyses the viability of PES models in the Amazon region, looking at the Latin America experiences. We will demonstrate that it is essential to identify the services provided by the ecosystem to determine supply and demand in the market. We will also show that the viability of the schemes depend on the capacity of the agents for contracting, which demand an accurate analysis about property rights on the selected regions. Under the Brazilian law, so far, there is no explicit recognition of the environmental services to enable a financing system that could be used to recover deforested lands and also guarantee the accomplishment of environmental law.